Analisis Tingkat Kepercayaan Masyarakat: Kualitas Personal dan Relasional Perangkat Desa dalam Pengelolaan Dana - Wa Ode, Muhardiana; Anto, La Ode; Dharmawati, Tuti (Penerbit Goodwood, 2025)
Purpose: This study aims to analyse the level of public trust in village officials in the management of village funds, focusing on personal and relational aspects. Methodology/ Approach: The research uses a quantitative method with a population of all residents of Village X aged 17 years and above, and a sample of 112 people selected through random sampling. Data were collected using a trust scale that had been tested for validity and reliability. Results: The regression analysis results show that benevolence (? = 0,401) and competence (? = 0,335) from the personal quality aspect have a significant effect on trust, contributing 42.5%. However, integrity did not show a significant effect. From the relational quality aspect, only closeness was significant (p<0.05), while support and reciprocity had no effect. Limitations: This study has limitations in developing the concepts of integrity, support, and reciprocity effectively, and has not yet comprehensively explored other factors such as transparency and accountability. The generalization of the study's results is also limited due to the sample size, which is not large enough or representative. Contribution: This study concludes that the personal and relational qualities of village officials play an important role in building public trust, but the integrity and support of village officials need improvement for more transparent and accountable village fund management.